The Role of Strategic Flexibility in Increasing Innovation (Case Study of Employee Promotion Strategies in Furniture Manufacturing Company) - Diah Nur Kusumawardhani; Deden A. Wahab Sya'roni (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
Innovation is needed for every business organization, especially in the furniture manufacturing company, where business competition is getting faster and tighter, because it is believed to be a driver of business performance. This study aims to determine the antecedents of innovation in furniture manufacturing companies in Cimahi City. This research was conducted on 30 respondents who are currently undergoing the A Few Good Men program. The results of the study were obtained from the respondents' monthly evaluation data and analyzed quantitatively. Data analysis was performed using simple random sampling and descriptive quantitative method was also used to collect the data needed for this research. The results of hypothesis testing indicate that the flexibility of the promotion strategy applied has an effect on increasing innovation in the company. So, the conclusion obtained is that the more flexible the strategy applied to the Furniture Manufacturing company, the higher the company's innovation invent.